Identifying Risks on Ibrahim Al-Khalil Street in Al-Masfalah Neighborhood in Makkah Al-Mukarramah from a Security and Safety Perspective - Bashawri, Abdulrahman (Journal of King Abdulaziz University: Environmental Design Sciences, 2023)
The study aims to identify a number of risks on Ibrahim Al-Khalil Street in the Al- Masfalah district, one of the most important and famous tourist areas in Mecca. Ibrahim Al-Khalil Street is considered one of the most important streets in Mecca due to its proximity to the Holy Mosque and the towers and shopping centers it contains for pilgrims and Umrah performers. The aim of the study was to discover the various threats and understand their causes. The main risks studied in the area include electrocution risks, collapse risks of old houses, flash flood risks, heat stress risks, pollution risks, and human behavior risks. Field research showed that there are many violations and wrong practices that may lead to harm to health or lives, including: the appearance of electrical cables on the roads, which may cause electric shock, especially during rain. The protrusion of bolts fixing lighting poles, which may cause serious injuries, the random distribution of power stations, which hinders pedestrian movement, and interference between vehicles and collisions. Irregular placement and accumulation of air conditioning devices in the narrow corridors of the entrances to some buildings and residences, which may lead to high temperatures and the outbreak of fires. Field studies of Ibrahim Al-Khalil Street showed the spread of some construction violations and risks, including: renovation activities and works for hotels during the Hajj season, as well as the presence of a number of old and dilapidated buildings that are still used for housing purposes for pilgrims, Umrah performers, and workers. Temperatures and relative humidity were measured along Ibrahim Al-Khalil Street over a period of 7 days during the Hajj season in the period from (July 1-15, 2020 - Dhu al-Hijjah 1-15, 1443 AH). The results showed that temperatures reached high values exceeding 45 degrees Celsius, as well as the relative humidity reached approximately 40%. The climatic data of Zahrat Kudai station for the month of July was also used. The data measured for temperature and relative humidity during that period was used to calculate the rate of heat stress, which gave values ranging from 43-48 in that period, which indicates a high risk rate and the possibility of the occurrence of heat contractions and heat stress. ; Heatstroke is likely to occur with continued activity in these conditions. Noise rates were also measured on Ibrahim Al-Khalil Street, at different periods during the day and night. The results showed that noise levels exceeded the permissible limits (50 decibels) during daytime in residential areas and reached 72-79 decibels. There was also a noticeable increase in the percentage of different sizes of dust suspended in the air. The field survey of Ibrahim Al-Khalil Street showed the emergence of problems in crowd management, which in turn have a negative impact on the safety and health of pilgrims, including: interference between pedestrians and vehicular movement, the failure to specify special paths for pedestrians and vehicles, which may cause interference and collisions, and the absence of guidance and warning signs designated for crossing pedestrians entering the Holy Mosque in Mecca, using inappropriate barriers, which may cause injuries, not developing an announced plan for road users, which causes traffic confusion. The hydrological results also showed that there are two basins affecting the Ibrahim Street area, and morphometric coefficients were used to calculate the degree of danger of the basins and the extent of their impact.